A New Climate for Christology : Kenosis, Climate Change, and Befriending Nature - McFague, Sallie (Book collections on Project MUSE., 2021)
For decades, Sallie McFague lent her voice and her theological imagination to addressing and advocating for the most important issues of our time. In doing so, she influenced an entire generation and empowered countless people in their efforts to put religion in the service of meeting human needs in difficult times. In this final book, finished in the year before her death in 2019, McFague summarizes the work of a lifetime with a clear call to live in "such a way that all might flourish." The way, she argues, is the "kenotic interpretation of Christianity: the odd arrangement whereby in order to gain your life, you must lose it. The way of the cross is total self-emptying so that one can receive life, real life, and then pass this life on."A masterful and life-giving summing-up of a theology that makes a profound difference for us, our communities, and our planet.